Evaluation of change in surface enamel microhardness in patients undergoing fixed orthodontic appliance therapy - A randomized control trial - Ramya Rajendran; V Sudhakar; R Sumanth Rangarajan; Anandadevi Chinnasamy; G Vasupradha; J Sathiya Jeeva (Wolters Kluwer Medknow Publications, 2021)
Aim: This study aims at determining the amount of enamel decalcification in terms of microhardness. Materials and Methods: Twenty patients requiring treatment by extraction method for Class I malocclusion with bimaxillary protrusion were selected for the study. Twenty patients were randomly divided into control group and experimental group. In the control group (n = 40), extraction of permanent first premolars was done on day 1 of bonding to assess the Vickers hardness number (VHN) of enamel surface, and in the experimental group (n = 40), extraction of the contralateral premolars was done on the 28th day after bonding to assess the VHN of enamel surface. The values are tabulated and analyzed by SPSS software. Results: There is significant surface enamel dissolution of enamel crystals in the experimental group compared to the control group, and a statistically significant difference in VHN is evident between the control and experimental groups. The surface enamel dissolution (VHN) is not significant difference noted between mandibular and maxillary premolars of the control and experimental groups. Conclusion: The present study has demonstrated a higher level of surface enamel dissolution in the experimental group. There is a marked difference in the VHN between the control and experimental groups, which is statistically significant. The scanning electron microscopy study also confirms the presence of surface enamel demineralization following orthodontic bonding.